Analysis on the influencing factors of spatial correlation of haze pollution in North China: Experience research based on QAP analysis - Wang, Linshan; Liu, Chuanming; Xi, Yang (Archives of Business Research, 2020)
Based on the AQI daily data of Northern China from January 1, 2016 to December 31, 2018, this paper uses nonlinear Granger causality test technology to identify the spatial correlation of haze pollution, and from the perspective of relational data, adopt Quadratic Assignment Procedure (QAP) to investigate the influencing factors of the spatial correlation of haze pollution in northern China. This study finds that：(1) QAP correlation analysis shows that geographical distance matrix, difference in the development level of the tertiary industry and difference in the green space area of urban construction are correlated with haze pollution. (2) QAP regression analysis results show that geographic distance matrix, economic development level and environmental regulation level can explain why the adjustment factor of spatial correlation of haze pollution is 2.6%. The influence of geographical distance matrix on the spatial correlation network of haze pollution within the range of 0 300km has passed the significance test, which indicates that haze pollution has broken through the geographical proximity effect, and more distant cities also have spatial correlation of haze pollution.